If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9e + -1 = 2.6 Reorder the terms: -1 + 9e = 2.6 Solving -1 + 9e = 2.6 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9e = 2.6 + 1 Combine like terms: -1 + 1 = 0 0 + 9e = 2.6 + 1 9e = 2.6 + 1 Combine like terms: 2.6 + 1 = 3.6 9e = 3.6 Divide each side by '9'. e = 0.4 Simplifying e = 0.4
| 3(0)-6y=18 | | 3x-6(0)=18 | | 3x^3-4x^2+8x+8=0 | | 5p=29 | | 4x-2=x-17 | | 4.8g=15.36 | | 3x+4=18-4x | | 1.5z=7.5 | | 3x+4=2(2x+7) | | 121=11d | | -33-8x=8x+15 | | 9(a+2)=81 | | 5x-4(-10)=20 | | 5x-4(0)=20 | | 5(0)-4y=20 | | 27-2x=7x+15 | | 64x^2-1=0 | | 24=6c-6 | | 5e-5=10 | | 8(-8)+9(7)=x | | 6x+10=-50-9x | | 6p=54 | | 9x^2-9=0 | | 2z+5=1 | | x^2+15x+56=0 | | 8p-40=0 | | 5-8x=71-29x | | 27x-3(x-6)=6 | | x^2+x-42=0 | | 2k+k+3k= | | -92-9x=10x+22 | | 5x^2+11x+2=0 |